Case Report: An unexpected case of tumor regression in blue nevus melanoma following COVID-19 infection - Bracero, Yadriel; Nghiem, Emily; Singh, Ajay K.; Kenchappa, Divya B.; Berglas, Rachel; Fidvi, Shabnam; Kuang, Chaoyuan; Papalezova, Katia; McLellan, Beth; Amin, Bijal; Saenger, Yvonne M. (Frontiers in Immunology, 2025)
Blue nevus is a benign melanocytic lesion that appears as a blue or dark mole due to the presence of melanin deep within the skin. In rare cases melanoma can arise from this association with blue nevus, and entity termed blue nevus melanoma (BNM). BNM most frequently occurs on the scalp and is an aggressive subtype of melanoma which has the tendency to metastasize. Similar to acral melanoma, BNM has a distinct genetic profile, is less linked to sun exposure, and has an equal incidence in patients of European and non-European ancestry. It is also less responsive to immunotherapy. This case report describes a diagnosis of blue nevus-related scalp melanoma characterized by GNA11 mutation in a 50-year-old female Hispanic patient, with a tumor refractory to multiple courses of combination immunotherapy who developed metastases to the liver and underwent microwave ablation of the hepatic lesions. Her disease course was complicated by hospitalization for infection with coronavirus disease of 2019 (COVID-19) and autoimmune hepatitis. Months after being discharged, surveillance imaging revealed a decrease in size of the existing lesions without additional therapeutic intervention. While this unusual response can be attributed to multiple factors, this observation aligns with emerging reports suggesting potential tumor remission associated with COVID-19 infection.